Prevalence of headache in adolescents and association with use of computer and videogames - Xavier, Michelle Katherine Andrade; Pitangui, Ana Carolina Rodarti; Silva, Georgia Rodrigues Reis; Oliveira, Valéria Mayaly Alves de; Beltrão, Natália Barros; Araújo, Rodrigo Cappato de (Ciência & saude coletiva, 2015)
The aim of this study was to determine the prevalence of headache in adolescents and its association with excessive use of electronic devices and games. The sample comprised 954 adolescents of both sexes (14 to 19 years) who answered a questionnaire about use of computers and electronic games, presence of headache and physical activity. The binary and multinomial logistic regression, with significance level of 5% was used for inferential analysis. The prevalence of headache was 80.6%. The excessive use of electronics devices proved to be a risk factor (OR = 1.21) for headache. Subjects aged between 14 and 16 years were less likely to report headache (OR = 0.64). Regarding classification, 17.9% of adolescents had tension-type headache, 19.3% had migraine and 43.4% other types of headache. The adolescents aged form 14 to 16 years had lower chance (OR ≤ 0.68) to report the tension-type headache and other types of headache. The excessive use of digital equipment, electronic games and attending the third year of high school proved to be risk factors for migraine-type development (OR ≥ 1.84). There was a high prevalence of headache in adolescents and high-time use of electronic devices. We observed an association between excessive use of electronic devices and the presence of headache, and this habit is considered a risk factor, especially for the development of migraine-type.